Periprocedural Assessment of Paravalvular Regurgitation After Transcatheter Aortic Valve Replacement Using Diastolic Delta and Videodensitometry - Maxim J. P. Rooijakkers; Ahmed Elkoumy; Niels A. Stens; Marleen H. van Wely; Geert A. A. Versteeg; Tsung‐Ying Tsai; Laura Rodwell; Robin H. Heijmen; Patrick W. Serruys; Osama Soliman; Niels van Royen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Paravalvular regurgitation (PVR) is a common complication after transcatheter aortic valve replacement, posing an increased risk of heart failure and mortality. Accurate intraprocedural quantification of PVR is challenging. Both hemodynamic indices and videodensitometry can be used for intraprocedural assessment of PVR. We compared the predictive value of the isolated versus combined use of the hemodynamic index diastolic delta (DD) and videodensitometry for the incidence of relevant PVR 1 month after transcatheter aortic valve replacement. Methods and Results In this prospective cohort study, patients underwent periprocedural PVR assessment by DD and videodensitometry (using left ventricular outflow tract—aortic regurgitation [LVOT‐AR]). Cardiac magnetic resonance served as reference modality for PVR assessment. Relevant PVR was defined as cardiac magnetic resonance–regurgitant fraction >20%. Fifty‐one patients were enrolled in this study. Mean age was 80.6±5.2 years and 45.1% of patients were men. Mean LVOT‐AR and cardiac magnetic resonance–regurgitant fraction were 8.2%±7.8% and 11.7%±9.6%, respectively. The correlation between DD and LVOT‐AR was weak (r=−0.36). DD and LVOT‐AR showed a comparable accuracy to predict relevant PVR (area under the curve 0.82, 95% CI: 0.69–0.95 versus area area under the time–density curve 0.80, 95% CI: 0.62–0.99). The combination of DD and LVOT‐AR improved the prediction of relevant PVR (area under the time–density curve, 0.90, 95% CI: 0.81–0.99), and resulted in an increased concordance (86.3%) and positive predictive value (75%) compared with DD alone (76.5% and 40%, respectively), or LVOT‐AR alone (82.3% and 50%, respectively). Conclusions DD and videodensitometry are both accurate and feasible modalities for the assessment of PVR after transcatheter aortic valve replacement. The synergistic use of both techniques increases the predictive value for relevant PVR after transcatheter aortic valve replacement. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT04281771.